Management views and perspectives towards workplace and human capital disclosure in annual report - Yusri, Yusniyati; Amran, Azlan (School of Social Sciences, Universiti Sains Malaysia, 2012)
This research explores management views and awareness of corporate social responsibility towards the workplace and the importance to disclose and report workplace and human capital information in corporate annual reports. It has been reported from previous studies in CSR literature that companies disclosed more information related to employees as compared to other CSR dimensions; marketplace, community and environment. This research used qualitative approach in data collection by interviewing 13 senior managers from 10 public listed companies on their understanding and awareness of CSR towards workplace. The results showed that managers’ awareness and understanding of CSR are more on the involvement of company in community and environmental activities. Even though workplace is categorized as one of the components of CSR Framework, it is not perceived as one of the ‘social’ obligation of the company. However, company discloses and reports information of workplace and human capital because of its value human capital as the most valuable assets. As such, it is an obligation for companies to really take care of its employees and provide them with the best treatments as possible. The results also reported that companies disclose workplace and human capital information to attract potential and talented job seekers and enhance its image in the eyes of society.